Associations between force-time related single-leg counter movement jump variables, agility, and linear sprint in competitive youth male basketball players - BOZDOĞAN, TUBA (My University, 2023)
Background: Previous research has reported a strong relationship between vertical jumping, sprinting, and agility, as a reflection of lower-limb power. Unilateral analysis of this relationship has not yet been explored. This study primarily investigated the associations between single-leg countermovement jump (CMJ), sprint, and agility performances in youth basketball players. Methods: Thirty-five male basketball players from the youth category (age 15.06 +/- 2.62 years, n = 32 right-limb dominant; n = 3 left-limb dominant) performed single-leg CMJ, 20 m sprint, and T-drill agility tests over two sessions. Force-time-related performance variables were measured using a single-leg CMJ test on a Kistler force plate. Results: Significant moderate to large negative correlations were observed between single-leg CMJ variables, 20 m sprint, and T-drill agility, except for mean force for both dominant and non-dominant leg measures (r = -0.384 to -0.705). Mean power and mean force were correlated with the physical characteristics of the athletes for both legs (r = -0.389 to -0.843). Flight time and jump height were identified as the best predictor variables for both sprint and agility time in the stepwise model (R-2 = 0.608 to 0.660). No statistical inter-limb differences were found during the single-leg CMJ test (p > 0.05). Conclusions: The study findings suggest that youth basketball players with greater single-leg jump output most likely have better sprint and agility performances. Thus, trainers and athletic performance coaches may include unilateral limb exercises in their training programs to enhance lower-limb explosive performance and reduce limb asymmetries.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; adolescent; change of direction; speed; vertical jump; limb asymmetry; unilateral strength; team sports; INTER-LIMB ASYMMETRIES; EXPLOSIVE STRENGTH; ABILITY; PERFORMANCE; INTERRELATIONSHIPS; TESTS; POWER